Goh Keng Swee : a legacy of public service - Chew, Emrys; Kwa, Chong Guan (World Scientific, 2012)
"Dr. Goh Keng Swee's extensive career as a public servant was dynamic as well as distinguished, in many ways decisively instrumental in the making of the Republic of Singapore. This distinctive collection of essays attempts an assessment of the long-term influence and significance of Dr. Goh's major contributions. Commissioned as a companion volume to Goh Keng Swee: A Public Career Remembered, this volume brings together an exceptional team of Singaporean scholars whose interdisciplinary expertise and cross-generational perspectives offer a balanced analysis and nuanced appraisal of Dr. Goh's lifetime of public service. The book's contributors argue that Dr. Goh's past endeavours bequeathed an enduring legacy, meriting fresh examination and careful evaluation in order to appreciate the heroic scale of such achievement. Particularly instructive are the examples of Dr. Goh's thinking patriotism, fiscal prudence, strategic pragmatism, and creative imagination at work -- technocracy at its finest -- which could be of immediate, practical benefit to a wider 'nation of technocrats'. Further illumination comes from the insights of those contributors who had worked with the former Deputy Prime Minister and knew him personally."--Publisher's description.